Offshoring of It and it-enabled services: how far does India benefit from Its outsourcing industry - Bhattacharya, Anindya (Internext, 2008)
The literature on services offshoring typically focuses on the extent of job losses in the home country. The impact on recipient countries is rarely examined in the western debate on offshore outsourcing. The purpose of this paper is to analyze the impact of offshoring in information technology (IT) and IT-enabled services (ITES), including business process outsourcing (BPO), on employment creation and technology diffusion/innovation gap in India. The paper concludes that being a service industry, the IT/ITES sector cannot be expected to solve India’s massive unemployment problem. India needs to build labor-intensive, manufactured products, not just services, in order to create jobs for millions of educated but unemployed young Indians. Concerning technology diffusion/innovation gap, in spite of impressive progress achieved by Indian service providers, they continue to lag behind in high-end areas that call for creativity and innovation such as inventing innovative business products, and creating new global markets for such products.